Unpacking food to go: Packaging and food waste of on the go provisioning practices in the UK. Issue 126 (November 2021) - Hirth, Steffen; Boons, Frank; Doherty, Bob
Highlights: Food on-the-go is part of long-term trends towards convenience and eating out. Learning History-approach analyses OTG's complex social-ecological processes. Intersecting changes in urban planning, technology, domestic and corporate economy. OTG's emergence sheds new light on the dynamics of consumer responsibilisation. Pre-consumer types of waste generated by OTG provisioning need critical assessment. Abstract: In the emergent literature, food 'on-the-go' (OTG) tends to be addressed as a consumption trend. However, considering that it entails significant amounts of packaging and food waste and has seen enormous growth in the UK since the 1990s, it is not sufficiently understood how OTG emerged as a sector. Conceptualising OTG as a provisioning practice and adopting a 'Learning History' approach, we aggregate journalistic columns and expert interviews into lineages that explain sectoral developments over time, and we ask how stakeholders frame OTG's emergence and linked waste issues. We first show how OTG derives from an interplay of actors and shifts in socio-spatial organisation within the four areas of domestic economy and convenience, health and environment, urban space and policy, and corporate economy and technology. Subsequently, we outline typical understandings of packaging and food waste and shortcomings therein. Extending debates on consumer responsibilisation, we identify narratives that sideline producers' focus on growth and their role in shaping OTG provision. Stakeholders often frame (1) OTG as demand-driven by reference to an ostensible 'convenience culture', (2) material waste as an issue of the 'consumer-facing' end of the supply chain, i.e. concerning food wrappers rather than materials used 'back-of-store' for logistics, processing, and hygiene and (3) food waste as a matter of avoiding leftovers while taking for granted resource-intensive, "wasteful" foods as part of businesses' portfolios. We conclude that addressing waste higher up the supply chain may allow for a more nuanced account of causes of, and solutions to, unsustainable provisioning practices.